Attitudes towards Change and Organizational Performance: A Conceptual Discussion - Zakaria, Ashiah; Abdullah, Haim Hilman; Chuah, Chin Wei (2017)
Employees’ attitudes towards change and organizational performance are extremely interrelated each other hence approving that the performance of organization is exaggerated through the attitudes of employees towards change.The literature shows that successful organizational change and performance are determined by the willingness to embrace change. Thus, the purpose of this paper is to discuss the conceptualization of attitudes towards change to reduce resistance for change initiative which therefore impacts the outcomes and performance of organization.